'Live more': Study protocol for a community-based lifestyle education program addressing non-communicable diseases in low-literacy areas of the South Pacific. (December 2015) - Kent, L.; Reierson, P.; Morton, D.
Abstract Background Non-communicable diseases (NCDs) have reached epidemic proportions in Pacific Island countries. Unhealthy lifestyle is one of the major risk factors and lifestyle interventions have been shown to be efficacious for primary, secondary and early tertiary prevention. However, there is a paucity of evidence regarding effective community-based lifestyle interventions in the Pacific Islands. The Complete Health Improvement Program for high-income countries was contextualised for rural communities with relatively low-literacy rates in low-income countries using the REFLECT delivery approach. This study will assess the effect of this 'Live More' program to reduce participant's NCD risk factors and improve lifestyle behaviours associated with health and wellbeing, in low-literacy communities in countries of the South Pacific. Methods/Design This study is a 6-month cluster-randomised controlled trial of 288 adults (equal proportions of men and women aged 18 years and over) with waist circumference of ≥92 cm for men and ≥80 cm for women in four rural villages in each of Fiji, Vanuatu and Solomon Islands. Participants will permanently reside in their village and be able to prepare their own meals. Two villages will be randomised to the 'Live More' intervention (n  = 24) or to control receiving only country specific Ministry of Health literature (n  = 24). Intervention participants will meet three times a week in the first month, then once a week for the next two months and once a month for the last three months. Themes covered include: NCDs and their causes; and the benefits of positive lifestyle choices, positive psychology, stress management, forgiveness and self-worth, and how these influence long-term health habits. Outcome assessments at baseline, 30-days, 3-months and 6-months include body mass index, waist circumference, blood lipids, blood pressure and blood glucose. Secondary outcomes include changes in medication and substance use, diet, physical activity, emotional health and supportive relationships, collected by lifestyle questionnaire at the same time points. Discussion This is the first lifestyle intervention using the Reflect approach to target NCDs. The findings from the study will be used to guide broader delivery of a lifestyle intervention to improve health and wellbeing across the South Pacific. Trial registration Australian New Zealand Clinical Trials RegistryACTRN12614001206617 .